2021
DOI: 10.1002/mame.202100628
|View full text |Cite
|
Sign up to set email alerts
|

UV‐Shielding Performance and Color of Lignin and its Application to Sunscreen

Abstract: The balance between sunscreen performance and color is a main obstacle in the preparation of high-quality lignin-based sunscreens. In this study, five lignin samples (i.e., NaOH-L, EG-L, G-L, 1,3-PDO-L, and 1,4-BDO-L) are extracted from sugarcane bagasse by using five different solvent systems. The lignin extracted by organic solvents clearly shows light color and excellent UV-shielding performance, and the 1,3-PDO-L sample reveals the lowest total color difference (𝚫E is 30.4) and highest sun protection fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…According to reports, when lignin is added to commercially available sunscreens, the π−π* aromatic ring stacking between the lignin and the active substance of the commercially available sunscreen forms a larger conjugated structure, which synergistically improves the UV radiation resistance of the resulting emulsion. 38 The addition of 5% lignin to a sunscreen with SPF = 19 increased the sun protection performance up to SPF = 38. The addition of a sunscreen with SPF = 55 increased the sun protection performance up to SPF = 86 (Table 5).…”
Section: ■ Results and Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…According to reports, when lignin is added to commercially available sunscreens, the π−π* aromatic ring stacking between the lignin and the active substance of the commercially available sunscreen forms a larger conjugated structure, which synergistically improves the UV radiation resistance of the resulting emulsion. 38 The addition of 5% lignin to a sunscreen with SPF = 19 increased the sun protection performance up to SPF = 38. The addition of a sunscreen with SPF = 55 increased the sun protection performance up to SPF = 86 (Table 5).…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…Pure creams can barely block UV rays, and a small amount of added lignin can obviously decrease UV transmission (Figure D). According to reports, when lignin is added to commercially available sunscreens, the π–π* aromatic ring stacking between the lignin and the active substance of the commercially available sunscreen forms a larger conjugated structure, which synergistically improves the UV radiation resistance of the resulting emulsion . The addition of 5% lignin to a sunscreen with SPF = 19 increased the sun protection performance up to SPF = 38.…”
Section: Resultsmentioning
confidence: 99%
“…After blocking the phenolic hydroxyl groups of lignin through acetylation modification, the anti -UV radiation protection of lignin significantly decreased . Our previous study has also shown that phenolic hydroxyl groups greatly contribute to UV-shielding performance of polyol lignin . Researchers have also pointed out that when preparing colloidal spheres with EHL, the auxochromes in EHL such as hydroxyl and methoxy rise to the surface of colloidal spheres, promoting the UV absorption of colloidal spheres to the UVB region .…”
Section: Introductionmentioning
confidence: 96%
“…While large amounts of UVC and some UVB light are filtered and absorbed by the ozone layer of the stratosphere, the remaining UVA, UVB, and UVC light can reach the surface of the earth and damage human skin. , UVA can penetrate up to the dermis layer of the skin, affecting skin elasticity and causing wrinkles . UVB radiation can induce nucleic acid or protein denaturation in the skin cells, resulting in conditions such as acute dermatitis, skin cancer, and actinic keratosis. , UVC can also cause apoptosis and burning of the skin; furthermore, long-term exposure to even short periods of medium-intensity UVC irradiation can cause skin cancer …”
Section: Introductionmentioning
confidence: 99%
“…4 UVB radiation can induce nucleic acid or protein denaturation in the skin cells, resulting in conditions such as acute dermatitis, skin cancer, and actinic keratosis. 5,6 UVC can also cause apoptosis and burning of the skin; furthermore, long-term exposure to even short periods of medium-intensity UVC irradiation can cause skin cancer. 7 Sunscreens are widely used for protection from UV radiation as they contain UV filters to absorb or reflect light and prevent UV-induced skin damage.…”
Section: Introductionmentioning
confidence: 99%